Justified Rejection of the Policy of Granting Tax Incentives to Donor Companies: A Call to Protect the Idea of CSR from Distortion - SALEH, Younis A. Battal (Journal of Tourism Economics and Policy, 2025)
This article aims to highlight the distortions that the thought of CSR is exposed to due to the policy of granting tax incentives to donor companies adopted by legislative bodies in many countries of the world. The researcher adopted the method of logical justification and rational argumentation in describing and identifying the distortions that the thought of CSR is exposed to due to the adoption of this policy (By studying and analyzing the extent to which this policy is compatible with the content of CSR thought). This article identified all the distortions that the idea of CSR is exposed to due to the adoption of a policy of granting tax incentives to donor companies. This research article will enhance the intellectual capabilities of specialists in tax legislation. The logical justification and rational arguments raised in this article can be a pressure tool towards developing the laws of tax treatment of corporate donations in many countries of the world, with the aim of protecting the idea of CSR from distortion.